Percepatan Perhitungan Hasil Tes Sistem Online menggunakan Kompresi Database - Surya Sujarwo (Bina Nusantara University, 2013)
The article explores the influence of database compression on processing time in generating online test results through experimental study. The study uses three level compressions consists of none, row and page in table used by online test system. The experiment shows that using page compression results in faster processing time and less space compared to none and row compression, and the optimal row for compression is between 1001 and 2000 rows. In summary, to reduce space usage and processing time, it is better to use page compression in user answer table of online test system and to group the participant in schedule so that users’ answer will be between 1001 and 2000 rows.